COMPARATIVE ANALYSIS OF TAMSULOSIN AND TADALAFIL AS MEDICAL EXPULSIVE THERAPY FOR URETERAL STONES - SEERWAN, M; AHMAD, I; ADNAN, M; SHAFI, H; SAIFULLAH; HUSSAIN, M (Biological and Clinical Sciences Research Journal, 2023)
This study was designed to compare the efficacy of placebo, tamsulosin and tadalafil as expulsive medical therapy for removing distal ureteral stones. The prospective study was conducted in Multan, DI Khan & Lahore, from November 2021 to November 2022. The study included 129 subjects with distal ureteral stones sized ≤10mm. Subjects were randomly categorized into 3 groups, A, B and C, with 43 subjects each. Group A was administered tamsulosin 0.4 mg O.D., Group B was administered tadalafil 10 mg O.D. Subjects underwent therapy for 4 weeks. Duration and rate of stone expulsion, time and dose of NSAIDs, adverse effects and analgesic use of medication were recorded. The frequency of expulsion in groups A, B and C was 72.09%, 62.7% and 56.0%, respectively; this difference was statistically insignificant (p=.294). The mean expulsion time in groups A, B, and C was 17.65±1.2 days, 21.23±1.15 days and 22.35±1.16 days, respectively (p=.46). Frequency of endoscopic intervention after unsuccessful MET in groups A, B and C was 14 (32.5%), 18 (41.8%) and 20 (46.5%) respectively, the difference in frequency of endoscopic treatment among all groups was not significant (P=.294). Tamsulosin is a more effective MET for distal ureteral stones than tadalafil.